Localization of sustainable development goals in city strategies - Koroleva E. N., Sokolova U. A. (Strategies of Sustainable Development: Social, Law and External-economic Aspects, 2024)
The article presents brief results of defining sustainable development goals in the strategic goal-setting documents of the cities of the Samara region; recommendations are presented for transforming the strategic planning system with the prospect of forming ESG strategies for cities
Keywords: устойчивое развитие; sustainable development; стратегическое планирование; strategic planning; моногород; город; city; ESG-стратегия; single-industry city; ESG strategy